Phylogeographic analysis of the East Asian goldenrod (Solidago virgaurea complex, Asteraceae) reveals hidden ecological diversification with recurrent formation of ecotypes. (29th December 2017) - Sakaguchi, Shota; Kimura, Takuma; Kyan, Ryuta; Maki, Masayuki; Nishino, Takako; Ishikawa, Naoko; Nagano, Atsushi J; Honjo, Mie N; Yasugi, Masaki; Kudoh, Hiroshi; Li, Pan; Choi, Hyeok Jae; et al.
Abstract: Background and Aims: The processes and mechanisms underlying lineage diversification are major topics in evolutionary biology. Eurasian goldenrod species of the Solidago virgaurea complex show remarkable morphological and ecological diversity in the Japanese Archipelago, with ecotypic taxa well adapted to specific environments (climate, edaphic conditions and disturbance regimes). The species complex is a suitable model to investigate the evolutionary processes of actively speciating plant groups, due to its ability to evolve in relation to environmental adaptation and its historical population dynamics. Methods: Two chloroplast markers, 18 nuclear microsatellite markers and ddRAD-sequencing were used to infer population genetic demography of S. virgaurea complex with its related species/genera. Key Results: Our analysis showed that populations in Japan form an evolutionary unit, which was genetically diverged from adjacent continental populations. The phylogenetic structure within the archipelago strongly corresponds to the geography, but interestingly there is no concordance between genetic structure and ecotypic boundaries; neighbouring populations of distinct ecotypes share a genetic background. Conclusions: We propose that the traits specific to the ecotypic entities are maintained by natural selection or are very recently generated and have little effect on the genomes, making genome-wide genetic markers unsuitable for detecting ecotypic differentiation. Furthermore, some sporadically distributed taxa (found as rheophytes and alpine plants) were repeatedly generated from a more widespread taxon in geographically distant areas by means of selection. Overall, this study showed that the goldenrod complex has a high ability to evolve, enabling rapid ecological diversification over a recent timeframe.